Successful conversion surgery for gastric cancer with multiple liver metastases treated after S-1 plus cisplatin combination chemotherapy: a case report - Masashi Tsunematsu; Naoto Takahashi; Keishiro Murakami; Takeyuki Misawa; Tadashi Akiba; Katsuhiko Yanaga (Surgical Case Reports)
Abstract Background Gastric cancer with multiple liver metastases have poor prognosis. Recently, stage IV gastric cancer patients who respond well to systemic chemotherapy can be treated by gastrectomy. We herein report a case of advanced gastric cancer with liver metastases who was successfully downstaged by systemic chemotherapy and underwent conversion surgery. Case presentation A 60-year-old male patient was diagnosed with gastric cancer with multiple liver metastases [cT3N3M1, stage IV]. After 18 courses of S-1 plus cisplatin combination chemotherapy (S-1 administered orally (80 mg/m2/day) twice a day for 21 consecutive days and cisplatin (60 mg/m2) infused on day 8), marked regression of liver metastasis was achieved, and we performed open total gastrectomy with D2 lymph node dissection. The patient was discharged from the hospital 10 days after the operation. Histopathological examination revealed no malignant cells in the lymph nodes [ypT1bN0M0, stage IA]. S-1 as the adjuvant chemotherapy was administered for 12 months, and the patient is alive without a recurrence for 33 months after surgery. Conclusions Conversion surgery may improve the poor prognosis of gastric cancer.